1998
DOI: 10.1203/00006450-199806000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fish Oil and α-Tocopherol in Immunoglobulin A Nephropathy in the Rat

Abstract: Alpha-tocopherol and fish oil have been reported to modulate the progression of IgA nephropathy in animals and humans. Because fish oil has been reported to exacerbate renal disease in subtotal nephrectomized rats, we investigated the effects of fish oil, with and without alpha-tocopherol, on the course of IgA nephropathy. Experimental IgA nephropathy was induced in male Sprague-Dawley rats, weighing 170-200 g, by oral and i.v. immunization with bovine gamma-globulin for 8 wk. IgA nephropathy was evidenced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…More recently, Branten et al [75] demonstrated no difference between fish oil-treated and untreated controls with IgA nephropathy. It is important to note that the beneficial effects of fish oil may be a consequence of the vitamin E in the fish oil preparation, as shown in experimental IgA nephropathy [76]. These unresolved issues about the use of fish oils demand a careful re-appraisal of its long-term efficacy [77, 78].…”
Section: Clinical Studies In Prevention Of Progression In Iga Nephropmentioning
confidence: 99%
“…More recently, Branten et al [75] demonstrated no difference between fish oil-treated and untreated controls with IgA nephropathy. It is important to note that the beneficial effects of fish oil may be a consequence of the vitamin E in the fish oil preparation, as shown in experimental IgA nephropathy [76]. These unresolved issues about the use of fish oils demand a careful re-appraisal of its long-term efficacy [77, 78].…”
Section: Clinical Studies In Prevention Of Progression In Iga Nephropmentioning
confidence: 99%
“…10 The beneficial effect of fish oil in glomerulosclerosis is likely due to vitamin E supplementation. 11,12 Neoplastic proliferation and arteriosclerotic lesions are inhibited by d-alpha-tocopherol. The proliferation activated by platelet-derived growth factor is particularly sensitive to d-alpha-tocopherol.…”
Section: Discussionmentioning
confidence: 99%
“…Control animals received no BGG throughout the experiment; they were given 6 mM HCl in tap water to drink and 0.2 ml of normal saline intravenously for 3 consecutive days at the end of the experiment. 15 IgA nephropathy model Rats were orally immunized with 0.1% BGG (G7516; Sigma Chemical (St. Louis, MO, USA) in a 6-mM HCl solution as the drinking water 16 for 4 weeks. A second group received BGG in this way for 6 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…16 Rats were then killed by exsanguination under general anesthesia as described in our previous studies. [13][14][15] All animals were exsanguinated via a catheter placed in the aorta, just below the renal arteries, and blood was saved for α-tocopherol and malondialdehyde (MDA) analysis. Before the right kidney was harvested, the inferior vena cava was incised, and perfusion via the aorta with 0.9% NaCl was performed to remove circulating erythrocytes from the kidney.…”
Section: Methodsmentioning
confidence: 99%